Analyzing Speaking Problems Faced by Efl Colleges Learners - Anita Suciati Rahayu; Erika Ayu Anggraeni; Irfan Saputra; Novia Umi Astari; Vegi Mahlul Betiya; Linda Septiyana (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
The purpose of this qualitative research is to examine what problems are faced by EFL Colleges Learners in speaking English especially at IAIN Metro, Lampung. The researcher took the fourth semester at English Department of IAIN Metro as the subject. The total numbers of the subjects were ten (10) students.  The researcher interviewed the students to find out about the EFL collages learners difficulties in speaking skill. The findings showed that there are four important themes which emerged in this study, namely (1) the students are lack of Vocabularies, (2) The grammar is not well mastered by the students, (3) the students are afraid of negative responses from others, and (4) the students have low self-confidence in speaking English.